Iluminação natural em salas de aula: análise de novos parâmetros normativos - Larissa Arêdes Monteiro (2023)
Normative instruments contribute to the evaluation of spaces in a quantitative and qualitative way, and evaluations that are more centered on the health of the occupant and that encompass the dynamics of natural light have been presented in international standards. The Brazilian standard NBR 15215-3 is being revised and should incorporate these new assessments with five criteria: availability of natural light, exterior view, glare, minimum insolation and exposure to direct sunlight. In order to analyze the applicability of the new normative parameters and the interference between them, the research sought to understand the incidence of natural light, the occurrence of glare and the quality of exterior views in higher education classrooms, using as a case study the building of the Center for Didactic Activities of Exact Sciences 3, at UFMG. A dynamic simulation of natural light in the spaces was carried out using Rhinoceros software with the ClimateStudio plug-in, considering the height of the visual field of the sitting and standing user, and varying the conditions of the natural light systems, comparing: the efficiency of existing systems, windows with provisions required by standards and the configurations of windows in the daily life of users. New glare control devices were also simulated to remedy visual discomfort, seeking balance between the other parameters. It was proposed to consider glare as critical whenever the Spatial Disturbing Glare (sDG) is greater than or equal to 0.38 in 5% of the time in 5% of the views. The mitigation of glare leads to a decrease in the availability of natural light and the view to the outside. However, in the case study, the use of horizontal louvers reduces glare by up to 59%, ensuring the autonomy of natural light and the view at satisfactory levels. The case study showed that analyzing only the availability of natural light and exposure to sunlight may not be enough for the analysis of visual quality, since in classrooms, in general, users cannot choose their viewing directions or your position. In these environments, glare becomes a predominant analysis phenomenon. It was also verified that it was not possible to meet all the criteria simultaneously for the seated user, and that these should be prioritized in each type of environment.